Painting Real : Warhol Wool Newman. - Pakesch, Peter; Hochdörfer, Achim; Pichler, Wolfram; Schmatz, Ferdinand; Huber, Hans Dieter; Höller, Christian; Bruno, Giuliana; Siegel, Marc; White, Ian; Kunsthaus Graz (Köln : Verlag der Buchhandlung Walter König, 2009)
Wool, Christopher ; Warhol, Andy ; Newman, Barnett ; Lockhart, Sharon ; Conner, Bruce
Kunsthaus Graz, Graz, September 26, 2009 until January 10, 2010
kunstcatalogus